Seismic Safety Assessment of Existing Low-rise RC Buildings with Rapid Visual Screenings and Preliminary Evaluation Methods - Moe Myat Myat Aung; Mya Nan Aye (Universitas Gadjah Mada, 2021)
Mandalay, the second largest city in Myanmar, is situated near the Sagaing Fault (the major fault in Myanmar). In the Mandalay region, the number of low-rise buildings is much greater than that of high-rise buildings. As such, seismic safety assessments of low-rise buildings play an important role in developing Mandalay as a smart city. In this study, the rapid visual screening (RVS) and preliminary evaluation for 26 numbers of three- to eight-story RC buildings were investigated with three different RVS and preliminary evaluation methods. Based on the RVS methods, the FEMA P154 Level 1 and 2 results gave the highest risk. With the Bangladesh method, the higher the story, the more vulnerable the building. Meanwhile, the Indian method showed a medium risk status. According to the preliminary evaluation, the assessed buildings need a detailed seismic evaluation, except for one building in the Indian method. Similarly, all buildings need a detailed evaluation in the Bangladesh method. The most convenient RVS and preliminary evaluation can be derived from these results for buildings in Mandalay, Myanmar. Moreover, a method can be developed for seismic safety assessments in other ASEAN countries with subsequent research.